2021
DOI: 10.3390/nano11123265
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of the Catalyst Structures on CO2 Activation on Catalyst Surfaces

Abstract: Utilizing CO2 as a sustainable carbon source to form valuable products requires activating it by active sites on catalyst surfaces. These active sites are usually in or below the nanometer scale. Some metals and metal oxides can catalyze the CO2 transformation reactions. On metal oxide-based catalysts, CO2 transformations are promoted significantly in the presence of surface oxygen vacancies or surface defect sites. Electrons transferable to the neutral CO2 molecule can be enriched on oxygen vacancies, which c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 195 publications
(361 reference statements)
0
51
0
Order By: Relevance
“…Pt–Sn–Al 2 O 3 catalysts (UOP Oleflex) have been commercially applied for the dehydrogenation process of light alkanes with noticeable olefin selectivity and yield. However, it was rarely investigated whether the dehydrogenation capability can be retained and if additional ODHE + DRE or DRE + RWGS reactions can occur in the copresence of ethane and CO 2 , which is desirable as analyzed in Section . It has been reported that oxide supports play an important role in CO 2 activation such as via acid site interaction or supply of oxygen vacancies. Thus, different oxides, γ-Al 2 O 3 (acidic, irreducible), CeO 2 (amphoteric, reducible), and SiO 2 (neutral, irreducible), were adopted here to support the PtSn-based catalysts. As shown in Figures S1 and a, both the PtSn 3 /CeO 2 and PtSn 3 /SiO 2 catalysts exhibited much lower ethane and CO 2 conversion (<3%) than PtSn 3 /γ-Al 2 O 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Pt–Sn–Al 2 O 3 catalysts (UOP Oleflex) have been commercially applied for the dehydrogenation process of light alkanes with noticeable olefin selectivity and yield. However, it was rarely investigated whether the dehydrogenation capability can be retained and if additional ODHE + DRE or DRE + RWGS reactions can occur in the copresence of ethane and CO 2 , which is desirable as analyzed in Section . It has been reported that oxide supports play an important role in CO 2 activation such as via acid site interaction or supply of oxygen vacancies. Thus, different oxides, γ-Al 2 O 3 (acidic, irreducible), CeO 2 (amphoteric, reducible), and SiO 2 (neutral, irreducible), were adopted here to support the PtSn-based catalysts. As shown in Figures S1 and a, both the PtSn 3 /CeO 2 and PtSn 3 /SiO 2 catalysts exhibited much lower ethane and CO 2 conversion (<3%) than PtSn 3 /γ-Al 2 O 3 .…”
Section: Resultsmentioning
confidence: 99%
“…It was increased in the order of PtSn/SiO 2 << PtCe/SiO 2 < PtSnCe/SiO 2 , the changing pattern of which coincides well with that of CO 2 conversion at the steady state of TOS ( Figure 1 b). It has been reported that CeO 2 with richer oxygen defects commonly leads to enhanced adsorption and activation of CO 2 [ 21 , 32 ]. Following this understanding, the greater amount of adsorbed CO 2 in the case of PtSnCe/SiO 2 than that of PtCe/SiO 2 can be reasonably ascribed to the presence of more oxygen defects of CeO 2 , as revealed by the Ce 3d XPS results ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of CO 2 activation, CeO 2 with a high oxygen-storage capacity and abundant oxygen defects was extensively investigated as a support/promoter/catalyst for the reactions involving CO 2 as a reactant [ 21 ]. In our previous study [ 22 ], CeO 2 and CeO 2 -based solid solutions were found to be effective for converting CO 2 into CO during the oxidative dehydrogenation of ethylbenzene with CO 2 , the ability of which is closely connected with oxygen defects over the oxides.…”
Section: Introductionmentioning
confidence: 99%
“…CO 2 is one of the most abundant greenhouse gases in the earth's atmosphere, and its capture, sequestration or chemical transformation into industrial feedstocks and fuel is a matter of great interest. Recent reviews have shown that both metal atoms 1 and extended metal surfaces 2 can activate molecular CO 2 effectively, the first mechanistic step in its transformation. Of particular interest to this study, Schwarz 1 has highlighted the crucial role that metal ions play in CO 2 reduction and the formation of new bonds involving carbon.…”
Section: Introductionmentioning
confidence: 99%